Постать Миколи Кащенка у контексті історії ХІХ - початку ХХ ст. - Готра, Олена Броніславівна (Чорноморський літопис, 2014)
Досліджено науково-педагогічну та громадську діяльність академіка М. Ф. Кащенка. Висвітлено біографію вченого за особовим архівним фондом. Розкрито пріоритетні напрями його діяльності, визначено місце і роль вченого у галузі біологічної науки, медицини та культури наприкінці ХІХ – першій третині ХХ ст.

The article is a research of scientific-pedagogical and public activities of academician M. Kashchenko, the biologists, embryologists, zoologists, the founder of the Siberian Horticulture, who actively participated in the creation of the Ukrainian Academy of Sciences. He headed the Physics and Mathematics Department of UAS, was the organizer and director of a big number of scientific institution sand organizations in the university centers of Ukraine and Russia. His pen includes over 200 scientific papers. M. Kashchenko is also famous as a teacher of high school, lecturer, populariser of scientific knowledge, writer and social activist. The biography of the scientist has been investigated through the documents of his personal fund. The main directions of his activity and the place and role of the scientist in biological science and medicine at the end of the XIXth – and at the beginning of the XXth centuries were analyzed in the article. In the article is shown citizenship of scientist during the First World War and the evaluation of its activities by the public. Materials were used from scientists Archives about the organization of courses of study medicinal plants. An importance of the scientist is researching in solving urgent social problems. The primary sources are valuable of family participation Academician M. Kashchenko during the First World War. Popularizing is noted of scientific knowledge and broad interests’ versatile scientist. The author was discovered the history of acclimatization garden. It is noted that the scientist enjoyed great prestige among faculty of the Kiev Polytechnic Institute; an important part of M. Kashchenko life’s journey took teaching activities, which he combined with scientific research. The scientist has a number of literary works: plays, poems, short stories and two fantastic stories that show a rich spiritual world academician
Keywords: М. Кащенко; вчений; професор; педагог; громадська діяльність; M. Kashchenko; scientist; professor; teacher; public activity